Multi-pulse laser wakefield acceleration - Jonnerby, J (2021)
This thesis presents results towards the realisation of high-repetition rate laser wakefield acceleration (LWFA). I have framed the contributions around the development of multi- pulse laser wakefield acceleration (MP-LWFA), which is a scheme using a train of laser pulses rather than a single pulse to excite a plasma wakefield. High energy but low peak power lasers that can reach multi-kHz repetition rates are already commercially available, and could become viable as drivers in the MP-LWFA scheme in the near future.